PRAGMATIC TRANSFER OF ALGERIAN LEARNERS IN LEARNING ENGLISH AS A THIRD LANGUAGE - Khadija, Belfarhi Allia (Indonesian Journal of Learning and Instruction, 2019)
The recent developments in cognitive linguistics turn EFL research interest to investigate the role of pragmatic aspects in the learn ability of English instead of grammar-governed learning. Pragmatics becomes ever more essential to the success of the language learner for its focus on language-in-use tasks. Pragmatic transfer occurs when non-native speakers of English transfer their L1 pragmatic knowledge to the target language. The EFL Algerian learner is closely concerned with pragmatic transfer since he/she speaks two languages, the first, Arabic, exhibits language distance with English while the second, French, is pragmatically more related to English than Arabic. The aim of the present research is to investigate the aspects of the pragmatic transfer and find out which language do learners transfer more from. To investigate the pragmatic transfer in the EFL Algerian classroom, we selected to work on the speech acts of requests among second year English students at Annaba University, through the use of discourse completion task. The analysis of data indicated the dominance of negative transfer of requests from Arabic to English. Algerian EFL learners transfer from Arabic to English and not from French despite the factor of language distance between Arabic and English.